2022
DOI: 10.1186/s13063-022-06280-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of acupuncture combined with language training for motor aphasia after stroke: study protocol for a multicenter randomized sham-controlled trial

Abstract: Background Motor aphasia after stroke is a common and intractable complication of stroke. Acupuncture and language training may be an alternative and effective approach. However, the efficacy of acupuncture and language training for motor aphasia after stroke has not been confirmed. The main objectives of this trial are to evaluate the effectiveness and safety of acupuncture and low-intensity, low-dose language training in treating ischemic motor aphasia after stroke from 15 to 90 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Based on these results, we chose 15 Hz/2 mA as the criterion for EA in our experiments. Our previous study [11] showed that EA at DU 26 could promote the proliferation of vascular endothelial cells around the infarct area in MCAO model rats. It is consistent with the present results, confirming that EA at DU 26 can promote angiogenesis of the penumbra following cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we chose 15 Hz/2 mA as the criterion for EA in our experiments. Our previous study [11] showed that EA at DU 26 could promote the proliferation of vascular endothelial cells around the infarct area in MCAO model rats. It is consistent with the present results, confirming that EA at DU 26 can promote angiogenesis of the penumbra following cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of collateral circulation following cerebral infarction includes early vasodilation (collateral circulation initiation) and subsequent angiogenesis (collateral circulation reconstruction). Cerebral infarction has been treated with acupuncture in the Tianjin University of Traditional Chinese Medicine First Affiliated Hospital for more than 30 years and Xingnao Kaiqiao method has been established [11] . Because acupuncture is effective, it plays an important role in promoting collateral circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The study protocol was approved by the ethics committee of the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine before participant enrollment ( Supplement 1 ). 23 We recruited outpatients from 3 tertiary hospitals in China, the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, the Changchun University of Chinese Medicine, and the Qilu Hospital of Shandong University, from October 21, 2019, to November 13, 2021. Written informed consent was obtained from all participants before randomization.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was approved by the ethics committee of the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine before participant enrollment (Supplement 1). 23…”
Section: Methodsmentioning
confidence: 99%